Chemical vapor deposition growth and characterization of two-dimensional hexagonal boron nitride - Tay, Roland Yingjie (2016)
Atomically thin hexagonal boron nitride (h-BN) film is a highly attractive dielectric and a crucial material for next-generation high performance two-dimensional (2D) heterostructure devices. In this thesis, controllable growth of 2D h-BN films on various substrates using chemical vapor deposition (CVD) is demonstrated. An atmospheric pressure CVD system is developed for h-BN growth using ammonia borane (AB) as precursor and the effects of various critical parameters are systematically investigated. The h-BN film grown on Cu substrate is substrate-position dependent due to gas flow dynamics, which result in an increase in nucleation density as well as domain size downstream along the quartz tube. The effects of other CVD parameters such as growth temperature, growth time and various precursor conditions are further examined. Importantly, a slight increase in the growth temperature of 50 °C (from 1000 to 1050 °C) resulted in a significant increase in average domain size of ~17-fold. This parametric study thus highlights the impact of the crucial parameters to control the growth of h-BN films in terms of domain sizes, film coverage and thickness of the films. The growth of h-BN films are further investigated using a metal-catalyst-free approach directly on amorphous SiO2/Si and quartz substrates. The as-grown films are continuous and smooth with no observable pinholes or wrinkles across the entire deposited surface. Varying thickness of ~2 to 25 nm can be obtained through process control. The crystallite sizes are small of ~25 nm, as determined by Raman spectroscopy, due to the random and uncontrolled nucleation. The absence of transfer process eliminates additional degradation to the film which is detrimental to device performance. In order to increase the size of the single-crystal h-BN domains, highly smoothened electropolished Cu foils are utilized to suppress the amount of nucleation and to enhance lateral growth of the 2D crystals. Large domains with size of up to ~35 µm2 which are hexagonal in shape are observed for the first time. This discovery is in contradiction to many theoretical works which revealed that 2D h-BN domains are mostly stable in the form of triangles because of their asymmetric N- and B-edge energies. Therefore, these hexagonal shaped h-BN domains are extensively characterized to prove its validity. This work verifies that h-BN domains are stable in the form of hexagons and open up new avenues for further theoretical exploration. A “multi-nucleation” approach to obtain mosaic single crystalline h-BN films is further explored. Aligned h-BN domains for over centimeter distances are achieved by using resolidfied Cu substrate with (110) surface orientation and the edge interactions between coalesced domains are investigated. Due to the strict epitaxial relationship between h-BN and Cu lattices, well-defined symmetric multifaceted shapes such as “butterfly” and “6-apex star” are formed by convergence between adjacent triangular or hexagonal shaped domains. Defect lines are generated along the grain boundaries of mirroring h-BN domains due to the two different polarities (BN and NB) and edges with the same termination. The triangular domains with truncated edges and alternatively hexagonal domains are rationalized with Wulff shapes that have minimum edge energy. This work establishes a complete study and reveals essential insights to the various issues on the in-plane coalescence of 2D materials with binary configuration. Lastly, a new single-source precursor, trimethylamine borane (TMAB), is successfully used for the first time to grow monolayer h-BN single crystals as well as few-layer C-doped h-BN (h-BCN) films. As compared to AB, TMAB is a much cheaper alternative making it highly attractive in a manufacturing perspective. Importantly, pristine 2D h-BN films with a wide band gap of ~6.1 eV can be achieved by limiting the sublimation temperature of TMAB at 40 °C, while C dopants are introduced to the h-BN films when the sublimation temperature is further increased. The h-BCN thin films displayed band gap narrowing effects due to substitutional C doping. The chemical structure of the h-BCN films can be perceived as the B atoms are partially substituted by C atoms in an h-BN matrix. This study thus provides new insights into the design and fabrication of large-area atomically thin h-BN/h-BCN films toward practical applications and suggests that other anime borane complexes can be potentially used to synthesize such films as well.